Упростите Выражение:
-(a-5) × (a+3) - (1-a)²

fyntikwotoxgtde fyntikwotoxgtde    1   31.01.2021 13:56    0

Ответы
likonady likonady  02.03.2021 14:00

Пошаговое объяснение:

-(а² - 5а + 3а -15) - (1 - 2а + а²) =

= -(а² - 2а  - 15) - 1 + 2а - а² =

= -а² + 2а  + 15 - 1 + 2а - а² =

= -2а² + 4а + 14

ПОКАЗАТЬ ОТВЕТЫ
sadpoli sadpoli  02.03.2021 14:00

Пошаговое объяснение:

-(a-5) × (a+3) - (1-a)² = -(а²+3а-5а-15) -( 1-2а+а²)=  -а²+2а+15 - 1+2а-а²=

=-2а²+4а+14

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика